A new method for assessing the trajectory of abandoned channels and its application in Late Miocene in Shijiutuo bulge, Bohai Bay Basin, East China. (February 2022) - Niu, Bo; Bao, Zhidong; Gao, Xingjun; Zhang, Chi; Zhou, Yanbin; Su, Jinchang; Zang, Dongsheng; Wei, Mingyang; Lu, Kai; Li, Zongfeng; Xu, Xiting; Hu, Xiangyang
Abstract: Since oil fields in eastern China have entered the high-water-cut stage, the focus of research on reservoir sandbodies accumulated by meandering river systems has expanded from facies association to architectural element levels. However, when characterizing the planform morphology of the abandoned channels, the inference of channel-fill trajectories is a challenging task. We therefore developed a new approach to calculate the dip angles of sandstone-mudstone interfaces at the inner and outer bank of abandoned-channel fills using the resistivity logs of horizontal wells. This method uses trigonometric relationships considering the investigation radius, dip angles, and the length of the changing segment of resistivity logs to calculate these dip angles, enabling the determination of the actual trajectory of the abandoned channel. Our method supplements and improves upon existing techniques for assessing the planform morphology of channel sandbodies. A well-log response classification scheme of meandering river reservoir was established from horizontal wells in the study area by describing the characteristics of the resistivity logs under different combinations of lithofacies to obtain a better understanding of the reservoir. We examined the meandering river sedimentary reservoir of the Minghuazhen Formation (Nm03) in the western block of the Shijiutuo uplift in the Bohai Bay Basin. Single-well data and the sand thickness distribution were used to predict the location of point bars. Combined with the well-log response from horizontal wells, we inferred that the cross-bar channel was intersected the middle part of horizontal well H1. Finally, the fine-scale distribution of different types of sedimentary units in the reservoir was established. Highlights: The accurate depiction of abandoned channels is theoretically and practically significant for the study of reservoir heterogeneity. A new approach for calculating the dip angles of the sand-mudstone interfaces by resistivity log of the horizontal well was advanced. Logging facies templates may be useful in the determination of the contact relationship between different sedimentary units in meandering rivers. The plane distribution pattern provides a robust basis and guidance for the depiction of abandoned channels.